Dexmedetomidine Protects Mouse Brain from Ischemia-Reperfusion Injury via Inhibiting Neuronal Autophagy through Up-Regulating HIF-1α - Luo, Cong; Ouyang, Ming-Wen; Fang, Ying-Ying; Li, Shu-Ji; Zhou, Quan; Fan, Jun; Qin, Zai-Sheng; Tao, Tao (Frontiers in Cellular Neuroscience, 2017)
Stroke is the leading cause of death in China and produces a heavy socio-economic burden in the past decades. Previous studies have shown that dexmedetomidine (DEX) is neuroprotective after cerebral ischemia. However, the role of autophagy during DEX-mediated neuroprotection after cerebral ischemia is still unknown. In this study, we found that post-conditioning with DEX and DEX+3-MA (autophagy inhibitor) reduced brain infarct size and improved neurological deficits compared with DEX+RAPA (autophagy inducer) 24 hours after transient middle cerebral occlusion (tMCAO) model in mice. DEX inhibited the neuronal autophagy in the peri-ischemic brain, and increased viability and decreased apoptosis of primary cultured neurons in oxygen-glucose deprivation (OGD) model. DEX induced expression of Bcl-1 and p62, while reduced the expression of microtubule-associated protein 1 light chain 3 (LC3) and Beclin 1 in primary cultured neurons through inhibition of apoptosis and autophagy. Meanwhile, DEX promoted the expression of hypoxia-inducible factor -1α (HIF-1α) both in vivo and in vitro, and 2ME2, an inhibitor of HIF-1α, could reverse DEX-induced autophagic inhibition. In conclusion, our study suggests that post-conditioning with DEX at the beginning of reperfusion protects mouse brain from ischemia-reperfusion injury via inhibition of neuronal autophagy by upregulation of HIF-1α, which provides a potential therapeutic treatment for acute ischemic injury.